RELATIONSHIPS AND SPATIAL DISTRIBUTION OF SPECIES IN NORTH ZAMARI RESERVE FOREST, THAYARWADDY, MYANMAR - Min Thant, Myo; Manh Hung, Bui (Journal of Forestry Science and Technology, 2018)
The study shows that dominant species of the old-growth forest is mainly Lanea coromandelica, Terminalia crenulata, Stereospermum colais, etc. The dominant species of the forest after 20 years of exploitation are usually Berrya mollis, Lagerstroemia speciosa… and the dominant species for the forest after 10 years of logging is Vitex pubescens, Cratoxylum ligustrinum, Xylia xylocarpa... The results of spatial relationship analysis between dominant species show that for the old-growth forest, the species tend to grow close together at a distance between 0 to 2.2 m, but with distance greater than 2.2 m, the species are repulsive. In contrast, the forest after 20 years and 10 years of logging, species are repulsive and attractive, respectively. In the old-growth forest, the spatial distribution of species is clustered for any distance from 0 to 3.5 m. In contrast, the spatial distribution for forests after 20 and 10 years of logging is clustered at any distance. A rate of good trees is old-growth forest is the highest. They are often in the top storey. And then, the forest after 20 and 10 years of exploitation are lower, respectively. On the contrary, the rate of the medium and bad trees is greatest in the forest after 10 years recorvery. And then gradually decrease in forest after 20 years restoration and old-growth forests.